2013
DOI: 10.1002/j.2333-8504.2013.tb02347.x
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing a Business Learning Outcomes Assessment to College Students Outside of the United States: Validity and Reliability Evidence

Abstract: Since its 1947 founding, ETS has conducted and disseminated scientific research to support its products and services, and to advance the measurement and education fields. In keeping with these goals, ETS is committed to making its research freely available to the professional community and to the general public. Published accounts of ETS research, including papers in the ETS Research Report series, undergo a formal peer-review process by ETS staff to ensure that they meet established scientific and professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…versus U.S.‐based programs when an assessment is given outside the United States. Ling () also demonstrated that regional differences may appear at the program level. The extent to which the program‐level variations of non‐U.S.–based programs resemble those of the U.S. programs remains a question worthy of investigation as one considers exporting assessments.…”
Section: Domain Analysis Evaluation and Generalization Componentsmentioning
confidence: 99%
See 3 more Smart Citations
“…versus U.S.‐based programs when an assessment is given outside the United States. Ling () also demonstrated that regional differences may appear at the program level. The extent to which the program‐level variations of non‐U.S.–based programs resemble those of the U.S. programs remains a question worthy of investigation as one considers exporting assessments.…”
Section: Domain Analysis Evaluation and Generalization Componentsmentioning
confidence: 99%
“…Ling () pointed to curricular differences, which may impact performance and interpretations of score differences for non‐U.S. versus U.S.‐based programs when an assessment is given outside the United States.…”
Section: Domain Analysis Evaluation and Generalization Componentsmentioning
confidence: 99%
See 2 more Smart Citations